Reproductive health policy‐makers: Comparing the influences of international and domestic institutions on abortion policy. (26th January 2018) - Forman‐Rabinovici, Aliza; Sommer, Udi
Abstract: Do policies protecting women's rights correspond with norm change at the state level or the level of international institutions? We examine this question, comparing domestic and international institutional activity in correlation with reproductive health policy change, specifically, abortion access policy. At the domestic level, we examine female legislators and policies set to encourage gender equality, namely, electoral gender quotas. In the international arena, our theory distinguishes regional from international inter‐governmental bodies. Original data with measurement innovations introduced here—including the Comparative Abortion Policy Index (CAPI1 and CAPI2)—are analysed for over 150 countries for close to two decades. We find a heretofore‐overlooked relationship between international entities and reproductive health. Gender quotas, however, do not correspond with the general association between female representation and pro‐women policy. When researchers and policy‐makers consider gender quotas to promote women's rights, they may be advised to encourage female political participation through more organic means. Abstract : Video Abstract